Petrogenesis of ultramafic and mafic rock series from the North Pyrenean Castillon massif (Ariège, France): evidence of magma–crust interactions in the Ordovician? - Kilzi, Mohammad A.; Grégoire, Michel; Driouch, Youssef; Benoit, Mathieu; Debat, Pierre; Bédard, L. Paul (Frontiers in Earth Science, 2026)
The Castillon massif, in the northern Pyrenees, features a complex of decimetric to metric ultramafic and mafic layers emplaced within metasedimentary series (from the bottom to the top: garnet, sillimanite, and kyanite-bearing gneisses and sillimanite + cordierite-bearing gneisses). Ultramafic and mafic layers and metasediments have been deformed and metamorphosed under granulitic facies conditions during the Hercynian orogenesis. The mineralogical, petrologic, and geochemical characteristics of the studied samples allow us to define two distinct series: 1) a pyroxene-bearing magmatic series (UM-M1) consisting of ultramafic (UM: dunites, harzburgites, and orthopyroxenites) and mafic (M1: norites, gabbro–norites, and gabbros) rocks; and 2) a pyroxene-free and hornblende-bearing series (M2; mela-, meso-, and leucogabbros). The leucogabbros exhibit some characteristics of anorthosites, including the high Al2O3 whole-rock content (31 wt%), high An content (An84–96) in plagioclase, weak rare earth element enrichment, and very positive Eu anomalies. We propose that the rocks of the ultramafic and pyroxene-bearing rock-series (UM-M1 series) are all associated with the same magmatic event and that the M2 series rocks are associated with a distinct separate event. Isotopic data suggest that these formations are Ordovician. The M2 rocks have juvenile Nd isotopic signatures (εNd(460) from +4.59 to +8.11), suggesting that they are derived from superheated alumina-rich basaltic or basaltic–andesite melts extracted from a relatively depleted mantle source. In contrast, most of the M1 rocks derived from parental basaltic melts show partially crustal contamination, with only a few clearly juvenile samples (εNd(460) from +0.45 to +6.59). We propose a geodynamic evolution for the Castillon massif involving a two-stage genesis and the emplacement of the two series. First, the emplacement of olivine-saturated basaltic melts in a deep metasedimentary crust resulted in the M1 series. The second step involves the emplacement of alumina-rich basaltic or basaltic–andesite melts to produce the M2 hornblende-bearing series (mela-, meso-, and leucogabbros) devoid of pyroxenes. The leucogabbros show strong similarities with common anorthosites although they have not been previously observed in the Variscan Pyrenees.